As escolas acordeonísticas a partir do documentário “O Milagre de Santa Luzia” - Xavier, Rossini Antônio da Silva (2018)
This research presents a mapping of the practice of the accordion in Brazil carried out taking as a main reference the series O milagre de Santa Luzia (The miracle of Saint Luzia), a panoramic documentary made for TV in 52 episodes about the instrument and its performers, which includes unanimities like the presenter Dominguinhos, Luiz Gonzaga, Sivuca, Mário Zan and Renato Borghetti, as well as names unknown to the general public, but which represent and enrich the practice of the instrument in the country. From this documentary, and from the crossing of data with other sources located in the course of the research, a classification of the main schools of accordion was carried out. In this work, schools are understood as stylistic groupings of musical strands with specific characteristics developed along the time in friction with sociocultural aspects, regional traditions and nacional and even internacional influencies. The model adopted in this study to observe the practice of accordion in the country considers the existence of five large schools, denominated as: gaúcha, pantaneira, sertaneja-caipira, nordestina and cosmopolita. It is presented their musical specificities, their influences, their forerunners, the most characteristic genres, as well are listed the most emblematic performers in the formation of each school and the main representatives of the instrument in the current music and its musical references.